2022
DOI: 10.4102/hsag.v27i0.1851
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to address conspiracy beliefs and misinformation on COVID-19 in South Africa: A narrative literature review

Abstract: Conspiracy theories and misinformation have been explored extensively however, strategies to minimise their impact in the context of coronavirus disease 2019 (COVID-19) vaccines are limited. This study aimed to explore strategies that can be used to reduce the negative effects of conspiracies and misinformation about SARS-CoV-2. This review was carried out based on accessed literature on beliefs in misinformation about the COVID-19 pandemic. A comprehensive search of databases, such as Google Scholar, EBSCOhos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…One of the most significant current discussions in relation to the rollout and uptake of COVID-19 vaccines is COVID-19 infodemic (Bam 2022 ; Majee et al 2022 ). The WHO ( 2022a , b ) refers to COVID-19 infodemic as the spread of a large amount of fake news, rumours and information that mislead the public about emerging health issues and disease outbreaks in digital and social media.…”
Section: Presentation Of the Themes And Sub-themes Integrated With Th...mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most significant current discussions in relation to the rollout and uptake of COVID-19 vaccines is COVID-19 infodemic (Bam 2022 ; Majee et al 2022 ). The WHO ( 2022a , b ) refers to COVID-19 infodemic as the spread of a large amount of fake news, rumours and information that mislead the public about emerging health issues and disease outbreaks in digital and social media.…”
Section: Presentation Of the Themes And Sub-themes Integrated With Th...mentioning
confidence: 99%
“…Health promotion is a process of enabling people to increase control over and improve their health through engagement in healthy behaviours to enhance the quality of life and well-being (Kumar & Preetha 2012 ). However, COVID-19 infodemic affected people’s control, as it continues to disseminate misconceptions, misinformation and conspiracy theories about the vaccine through social media (Bam 2022 ; Geng et al 2022 ). For instance, research confirmed that COVID-19 infodemic perpetuated a risk of vaccine hesitancy and refusal of mandated vaccination among students, which influenced their participation in learning and teaching activities (Bam 2022 ; Geng et al 2022 ; Potgieter et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fears about mandated vaccinations appearing on social media can cause fear and scepticism about vaccines, according to the Africa CDC (2021). Conspiracy theories and religious ideas published on social media are two common types of misinformation that influence user perception (Bam, 2021;Chou et al, 2021;Shahi et al, 2020a).…”
Section: Challenges To Vaccine Acceptancementioning
confidence: 99%
“…Vaccination has been widely recognised as a critical tool in preventing the spread of COVID-19, with human studies indicating that COVID-19 vaccines are 89% safe, with a low to moderate risk of serious disease among older individuals (Bam, 2021). Despite this, there has been growing vaccine scepticism in South Africa, with only 67% of those polled expressing certainty in getting vaccinated and the remaining 33% uncertain or against getting vaccinated (Bam, 2021).…”
Section: Introductionmentioning
confidence: 99%